Religion, religiosity and spirituality: Conceptual differences in Brazilian psychotherapists' point of view. - da Cunha, Vivian Fukumasu; Feliciano, Thayná Andressa Soares; Scorsolini‐Comin, Fabio (Counselling & Psychotherapy Research, 2024)
The study aimed at identifying conceptions of Brazilian psychotherapists about "religion," "religiosity" and "spirituality." This is an exploratory study with a qualitative approach. Twenty‐four psychotherapists from two cities, one in the state of São Paulo and the other in the state of Minas Gerais, with a mean of 10.54 years in clinical practice, participated in the study. The participants completed a semistructured interview, and the data were organised through content analysis. It was identified that the participants have vague or incomplete knowledge about these concepts and their differences when comparing the Psychology and Health literature. This seems to be justified by the historical–scientific social context of the training process and by the fact that they do not always attribute real importance to the theoretical precision of these terms in clinical management with their patients. The absence of more precise definitions and discussions of these concepts and terms can increase the chances of the issue being neglected or infrequently addressed in sessions. This can affect the performance, the bond with the patient and the behaviour itself in sessions.